Pengaruh Minat Beli, Karakteristik Produk Dan Penilaian Konsumen Terhadap Pembelian Produk Selama Pandemi Covid-19 Pada Pengguna Aplikasi Online Di Kota Medan - Asido Hermanto Lumban Gaol; Hares Kumar; Hendra Jonathan Sibarani (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2021)
The purpose of this study was to examine the effect of buying interest, product characteristics, and consumer ratings on product purchase decisions during the Covid-19 pandemic on online application users in Medan City. The research sample was 30 respondents. The results showed that buying interest, product characteristics, and consumer ratings had a significant partial effect on product purchase decisions during the Covid-19 pandemic on online application users in Medan City.